Tert-butylhydroquinone augments Nrf2-dependent resilience against oxidative stress and improves survival of ventilator-induced lung injury in mice - Veskemaa, Lilly; Graw, Jan A.; Pickerodt, Philipp A.; Taher, Mahdi; Boemke, Willehad; Gonzalez-Lopez, Adrian; Francis, Roland C. E. (American Journal of Physiology-Lung Cellular and Molecular Physiology, 2021)
Oxidative stress caused by mechanical ventilation contributes to the pathophysiology of ventilator-induced lung injury (VILI). A key mechanism maintaining redox balance is the upregulation of nuclear factor-erythroid-2-related factor 2 (Nrf2)-dependent antioxidant gene expression. We tested whether pretreatment with an Nrf2-antioxidant response element (ARE) pathway activator tert-butylhydroquinone (tBHQ) protects against VILI. Male C57BL/6J mice were pretreated with an intraperitoneal injection of tBHQ (n = 10), an equivalent volume of 3% ethanol (EtOH3%, vehicle, n = 13), or phosphate-buffered saline (controls, n = 10) and were then subjected to high tidal volume (HVT) ventilation for a maximum of 4 h. HVT ventilation severely impaired arterial oxygenation (PaO2 = 49 ± 7 mmHg, means ± SD) and respiratory system compliance, resulting in a 100% mortality among controls. Compared with controls, tBHQ improved arterial oxygenation (PaO2 = 90 ± 41 mmHg) and respiratory system compliance after HVT ventilation. In addition, tBHQ attenuated the HVT ventilation-induced development of lung edema and proinflammatory response, evidenced by lower concentrations of protein and proinflammatory cytokines (IL-1b and TNF-a) in the bronchoalveolar lavage fluid, respectively. Moreover, tBHQ enhanced the pulmonary redox capacity, indicated by enhanced Nrf2-depentent gene expression at baseline and by the highest total glutathione concentration after HVT ventilation among all groups. Overall, tBHQ pretreatment resulted in 60% survival (P < 0.001 vs. controls). Interestingly, compared with controls, EtOH3% reduced the proinflammatory response to HVT ventilation in the lung, resulting in 38.5% survival (P = 0.0054 vs. controls). In this murine model of VILI, tBHQ increases the pulmonary redox capacity by activating the Nrf2-ARE pathway and protects against VILI. These findings support the efficacy of pharmacological Nrf2-ARE pathway activation to increase resilience against oxidative stress during injurious mechanical ventilation.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Lung; Redox; TBHQ; Ventilation; VILI